PENGARUH MODEL PEMBELAJARAN MOVING CLASS TERHADAP MOTIVASI BELAJAR EKONOMI SISWA SMA NEGERI 1 KOTA PROBOLINGGO - RIZKY CAHYA IMANDA (Jurnal Pendidikan Ekonomi (JUPE), 2013)
This study discusses about the effect of moving class learning model against student motivation to learn economics SMA Negeri 1 Probolinggo. This study is explanatory research using a quantitative approach. Data collection techniques used were questionnaires, observations, interviews, and documentation. The research conducted in SMA Negeri 1 Probolinggo. This study is a population. Results of data analysis showed that the significance of F = 0.028 <alpha (0.05) or can be seen from F = 5,188> Ftable = 4,06, a significant difference between moving class learning model for student motivation. Adjusted Rsquare value obtained is 0.087. The conclusion is a significant difference between moving class learning model for student motivation. Keywords: moving class learning model, motivation to learn economics